Effect of lymph node examined count on accurate staging and survival of resected esophageal cancer. Issue 5 (7th April 2019) - Xia, Wenjie; Liu, Suyao; Mao, Qixing; Chen, Bing; Ma, Weidong; Dong, Gaochao; Xu, Lin; Jiang, Feng
Abstract : Background: We examined the association between numbers of lymph nodes examined (LNEs) and accurate staging and survival to determine the optimal LNE count during esophagectomy using data from the Surveillance, Epidemiology, and End Results (SEER) cancer registry and the Department of Thoracic Surgery of a single institution (SI). Methods: A total of 7356 EC patients met our inclusion criteria from the SEER database and 1275 patients from SI. We applied multivariate models to investigate the relationship between the LNE count and LN metastasis and cancer‐specific survival (CSS). Odds ratios (ORs) and hazard ratios (HRs) generated by the multivariate models were fitted with Locally Weighted Scatterplot Smoothing, and the structural breakpoints were determined by the Chow test. Results: Higher numbers of LNEs were linked to a higher proportion of LN metastasis and better CSS in both cohorts. Cut‐point analysis determined a threshold of LNEs of 12 for adenocarcinoma and 14 for esophageal squamous cell cancer (ESCC) considering accurate staging, and 15 for adenocarcinoma and 14 for ESCC considering OS. The cut‐points for CSS were examined in the SEER database and validated in the divided cohort from SI (all P  < 0.05). Conclusion: A greater number of LNEs are significantly associated with more accurate N staging and better survival in EC patients. We recommend 15 and 14 as the threshold LNE counts for adenocarcinoma and ESCC patients, respectively.